PENGARUH HARGA, KUALITAS PRODUK, DAN KETERSEDIAAN PRODUK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA UD. SUMBER REJEKI KABUPATEN JEMBER - Suliyana, Putri Mita; Soeliha, Siti; Sari, Rini Kartika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The purpose of the study was to determine the effect of price, product quality, and product availability on customer satisfaction through purchasing decisions as an intervening variable at UD. Sumber Rejeki Jember Regency. The sampling technique in this study was simple random sampling. Data analysis and hypothesis testing in this study were done using Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that price has a significant positive effect on purchasing decisions, price has a positive but insignificant effect on customer satisfaction, product quality has a significant positive effect on purchasing decisions, product quality has a positive but insignificant effect on customer satisfaction, product availability has a positive but insignificant effect on purchasing decisions, product availability has a positive but insignificant effect on customer satisfaction, and purchasing decisions have a significant positive effect on customer satisfaction. The results of the indirect effect hypothesis test show that the price variable has a significantly positive effect on customer satisfaction through purchasing decisions, product quality has a significantly positive effect on customer satisfaction through purchasing decisions, and product availability has a positive but insignificant effect on customer satisfaction through purchasing decisions.